Self-Care: Exploring Health Consumers’ Interaction with Mobile Health Applications - Anderson, Kevin (Curtin University, 2018)
Consumers with chronic conditions have access to a plethora of mobile applications (‘apps’) to manage their health. Qualitative research confirmed consumers’ willingness to engage with this technology. A checklist was designed to assess the quality and usability of health apps, and trialled 11 asthma and 17 hypertension apps, identifying variable yet generally substandard quality. A concept map incorporating blockchain technology subsequently proposed how improved functionality and connectivity can enhance use of consumers’ self-monitored health data.